2004
DOI: 10.1097/01.ju.0000130752.97414.c8
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Comparison of Type of Nephrostomy Drainage Following Percutaneous Nephrostolithotomy: Large Bore Versus Small Bore Versus Tubeless

Abstract: Tubeless PCNL is associated with the least postoperative pain, urinary leakage and hospital stay. Small bore nephrostomy drainage may be a reasonable option in patients in whom the incidence of stent dysuria is likely to be higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(142 citation statements)
references
References 4 publications
3
135
1
3
Order By: Relevance
“…Tubeless percutaneous nephrolithotomy was introduced in 1997 (7). Subsequently, several groups reported their results with tubeless PCNL in selected patients (8)(9)(10), however all studies excluded patients with concerns regarding bleeding, perforation, or residual stones requiring a second--look nephroscopy. The benefits shown in these select patients included decreased postoperative pain and hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Tubeless percutaneous nephrolithotomy was introduced in 1997 (7). Subsequently, several groups reported their results with tubeless PCNL in selected patients (8)(9)(10), however all studies excluded patients with concerns regarding bleeding, perforation, or residual stones requiring a second--look nephroscopy. The benefits shown in these select patients included decreased postoperative pain and hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Desai et al [4] conducted a study comparing tubeless, conventional large bore and small bore nephrostomy drainage and concluded that tubeless technique is associated with less morbidity. But they did not describe the size of the tract and the method of choosing Amplatz sheath.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies describing the exit strategies for PCNL to reduce postoperative pain, leak and hospital stay. But there are not many studies regarding entry strategy.Desai et al [4] conducted a study comparing tubeless, conventional large bore and small bore nephrostomy drainage and concluded that tubeless technique is associated with less morbidity. But they did not describe the size of the tract and the method of choosing Amplatz sheath.…”
mentioning
confidence: 99%
“…Desai et al (12) did comparative study of type of nephrostomy drainage following PCNL, i.e., large bore (20 Fr) versus small bore (9 Fr) versus tubeless PCNL. Large bore nephrostomy tube patients had significantly higher analgesic requirement (218 mg of diclofenac sodium) than small bore and tubeless patients (140 and 88 mg of diclofenac sodium, respectively).…”
Section: Discussionmentioning
confidence: 99%